MINERALOGICAL CONTROLS ON MINE DRAINAGE OF THE ABANDONED ERVEDOSA TIN MINE IN NORTH-EASTERN PORTUGAL - Gomes M.E.P.; Favas P.J.C. (My University, 2006)
The Ervedosa Mine, in north-eastern Portugal, has Sn-bearing quartz veins containing cassiterite and sulphides that cut Silurian schists and a Sn-bearing muscovite granite. These veins were mined for Sn and As2O3 until 1969. Cassiterite, the main Sn ore, has alternate lighter and darker growth-zones. The darker zones are richer in Fe, Nb, Ta and Ti, but poorer in Sn than the adjoining lighter zones. Exsolution blebs of ferrocolumbite, manganocolumbite, Ti ixiolite, rutile, ilmenite and rare wolframite were found in the darker zones. Arsenopyrite is the most abundant sulphide and contains inclusions of pyrrhotite, bismuth, bismuthinite and matildite. Other sulphides are pyrite, sphalerite, chalcopyrite and stannite. Secondary solid phases consisting mainly of hydrate sulphate complexes of Al, Fe, Ca and Mg (aluminocopiapite, copiapite, halotrichite, pickeringite, gypsum and alunogen, meta-alunogen) occur at the surface of the Sn-bearing quartz veins and their wall rocks (granite and schist), while oxides, hydroxides, arsenates and residual mineral phases (albite, muscovite and quartz) occur in mining tailings. Toxic acid mine waters (acid mine drainage AMD), which have high conductivity and significant concentrations of As, SO4 and metal (Cu, Zn, Pb, Fe, Mn, Cd, Ni and Co), occur in an area directly affected by the mine. Surface stream waters outside this area have low conductivity and a pH that is almost neutral. Metal and As concentrations are also lower. Stream waters within the impact area have an intermediate composition, falling between that of the AMD and the natural stream waters outside impact area. Waters associated directly with mineralised veins must not be used for human consumption or agriculture. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Silurian; Paleozoic::Silurian